Phylogenetic evolution and impact on the immunogenic response of the Avian Infectious Bronchitis virus - Sanmiguel Plazas, Rosa (2023)
Avian Infectious Bronchitis (IAB) is a viral disease that generates great economic losses in the poultry industry. Due to its structural components and particular immunogenic characteristics, the IB virus, the chicken coronavirus (Gallus gallus), has generated a great challenge for its control, given the emergence of different genotypes with global distribution with changing clinical manifestations. This has generated interest in the study and analysis of the dynamics of the phylogenetic evolution of the virus, as well as the impact on immunological activity, requiring the development of new vaccine strains based on the high variability of the S1 gene portion 1. In the present review, updated information on the phylogenetic evolution of IAV was compiled and the impact on the immunogenic response in poultry production systems is analysed.